A Crisis of Representation: Interests, Identities and Politics. Issue 1 (June 2019) - Verma, Vidhu
Abstract: The controversy over political representation of marginalised groups and the implementation of quotas or reservations for historical injustice constitutes the most salient current battlefront in the conflict over the politics of social justice. Debates about the assumptions of theories of political representation tend to focus on political institutions, and for the most part, tend to debate them within nation-states. I begin by examining the debate on group representation in the Indian context. This article suggests that there is much to be gained in understanding how representation is challenged by following the politics of disadvantaged groups involved in this debate. To overcome the limitations in these theories we need to challenge the basic categories in thinking about political representation, that is about formation of interests, participation, sites of politics, and assertions of claims for representation. The second section focuses on formation of Dalit interests and the arguments for political representation. It examines the way representations of social divisions become problematic and resisted in institutionalized practices and political discourses. The third section point to limitations in our current thinking about theories of representation and the challenges they face. I argue that differences and disagreements within marginalised groups and the potential for intra-group conflicts of interests is challenging. Since shared membership of a disadvantaged group is not sufficient to have success in political representation, we argue that group justice depends in part on the ability to overcome differences and to forge a common political strategy. I argue that representations are eventually battles for meaning in politics through which social identities are constructed in ways that support or contest systems of inclusion and exclusion.